2010
DOI: 10.3141/2193-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pedestrian Safety at Midblock Crossings, Porto Alegre, Brazil

Abstract: This paper proposes a method to evaluate the potential risk of pedestrian crashes at midblock crossings, which can be applied in developing countries. The method is quantitative because it uses modeling techniques to represent the relationship of risk factors with the occurrence of pedestrian crashes. Application of the method described here comprised the analysis of reported pedestrian crashes in the city of Porto Alegre, in southern Brazil, between 1998 and 2006, and the identification of midblock crossings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…This result was in consistent with Diogenes and Lindau [55] who found that crossings located close to bus stops experienced higher pedestrian crash rates.…”
Section: Discussionsupporting
confidence: 82%
“…This result was in consistent with Diogenes and Lindau [55] who found that crossings located close to bus stops experienced higher pedestrian crash rates.…”
Section: Discussionsupporting
confidence: 82%
“…However, pedestrian crash models for two-way rural roads are scant, particularly in developing countries. Some studies have been conducted in the United States, New Zealand, Brazil and India (Diogenes and Lindau, 2010;Harwood et al, 2008;Sharma and Landge, 2012;Turner et al, 2006;Wong and Kockelman, 2013). As a part of the AASHTO Highway Safety Manual preparation, a study was conducted by Harwood et al (2008) that found that average daily pedestrian volume, vehicle volume, and maximum roadway width crossed by pedestrians were statistically significant predictors of pedestrian crashes.…”
Section: Literature Reviewmentioning
confidence: 97%
“…One study in Brazil built a pedestrian crash model for midblocks of one-way and two-way city roads using a Poisson regression model with a variety of explanatory variables (Diogenes and Lindau, 2010). However, the selection of the sample midblock focused on those sites that have comprehensive pedestrian crash records, which makes the developed model biased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the current evaluation methods that assess pedestrian safety conditions on streets usually consider safety at intersections or midblock crossings (e.g., Carter et al, 2006;Cirianni and Leonardi, 2008;King et al, 2009 andDiogenes andLindau, 2010). However, pedestrians also require safety along the streets and at intersections.…”
Section: Introductionmentioning
confidence: 97%